The structural indicators and logistics costs evaluation of Kayseri Firms, ranked in Turkey's Top 1000 industrial enterprises - Senay Oğuztimur (Megaron, 2016)
This article present partial findings of research project titled 'Enhancing Logistics Sector As a Tool in Order to Improve the Competitiveness of Large Scale Manufacturing Industry in Kayseri', supported by Yıldız Technical University Scientific Research Project Coordination Department. This research is based on large industrial firms in Kayseri of which had achieved to be ranked in top 1000 industrial enterprises in 2014, the list of Istanbul Chamber of Industry. The purposes of the research are; to present the basic structural characteristic of the large scale manufacturing industry, planted in Kayseri and to state the factors which increase logistic cost of manufacturing industry firms. Opinions of firms have been set via face-to face survey and in-depth oral interviews. Collected data evaluated by qualitative research methods. These are the findings; regarding with the basic structural indicators, firms logistics performance and problems regarding with logistics activities of the firms respectively. According to first group of findings, the distribution of sectoral form and firm size does not indicate to a concentration sub-sectors of manufacturing industry. It is evident that "being close to railway" used to be quite important while today highways dominate the location selection. Second findings group comprise that except two, all of the firms prefer to work with logistics providers. Nevertheless, field research shows that "logistics providing" in Kayseri means "only transporting". The third group of findings refer that high transportation costs of highways inside Turkey adversely affect input and manufacturing costs that entrepreneurs do not prefer to reach far markets due to high logistics costs. This is such an important problem that it is pointed as one of the most prominent issue to reach to new, far foreign markets.